Evolução e perspectivas do comércio internacional de açúcar e álcool - Moreira, Eduardo Fernandes Pestana (2007)
This work aims at showing predictions to sugar and ethanol international markets as well as to the brazilian share in this market. In order to achieve this task, it was presented a production and trade evolution panel of this industry since its constitution at the beginning of the capitalist system, whether in Brazil or in the whole world, where the concrete evolution of this industry is confronted with the national policies for the promotion and protection of each country and to the international agreements and negotiations in course, for the sugar industry as well as the whole agriculture sector. This last aspect is treated with particular concern, since the evolution of the sugar industry does not result exclusively from the soil and climate conditions of all world areas and regions, not even from the material basis constructed during the centuries, but also and mainly by the rules and policy mechanisms each country practices in order to support theirs national capitals. A survey of the literature of the possible scenarios in the economic and political hegemony disputes and the perspectives of international trade negotiations in course was done in order to support the assumptions framework that permitted the scenarios construction process. The methodologies used in this process were the cross impacts matrices and morphological analysis, which permitted to work with force relations among actors and with a large number of qualitative variables that keep a high level of dependence among them. It was built four alternative scenarios and from the projections of economic, fuel consumption and population s growth of several international institutions, it was developed quantitative predictions of this market